Intraoperative Cone‐Beam Computed Tomography and Multi‐Slice Computed Tomography in Temporal Bone Imaging for Surgical Treatment. (29th October 2013) - Erovic, Boban M.; Chan, Harley H. L.; Daly, Michael J.; Pothier, David D.; Yu, Eugene; Coulson, Chris; Lai, Philip; Irish, Jonathan C.
Abstract : Objective: Conventional computed tomography (CT) imaging is the standard imaging technique for temporal bone diseases, whereas cone‐beam CT (CBCT) imaging is a very fast imaging tool with a significant less radiation dose compared with conventional CT. We hypothesize that a system for intraoperative cone‐beam CT provides comparable image quality to diagnostic CT for identifying temporal bone anatomical landmarks in cadaveric specimens. Study Design: Cross‐sectional study. Setting: University tertiary care facility. Subjects and Methods: Twenty cadaveric temporal bones were affixed into a head phantom and scanned with both a prototype cone‐beam CT C‐arm and multislice helical CT. Imaging performance was evaluated by 3 otologic surgeons and 1 head and neck radiologist. Participants were presented images in a randomized order and completed landmark identification questionnaires covering 21 structures. Results: CBCT and multislice CT have comparable performance in identifying temporal structures. Three otologic surgeons indicated that CBCT provided statistically equivalent performance for 19 of 21 landmarks, with CBCT superior to CT for the chorda tympani and inferior for the crura of the stapes. Subgroup analysis showed that CBCT performed superiorly for temporal bone structures compared with CT. The radiologist rated CBCT and CT as statistically equivalent for 18 of 21 landmarks, with CT superior to CBCT for the crura of stapes, chorda tympani, and sigmoid sinus. Conclusion: CBCT provides comparable image quality to conventional CT for temporal bone anatomical sites in cadaveric specimens. Clinical applications of low‐dose CBCT imaging in surgical planning, intraoperative guidance, and postoperative assessment are promising but require further investigation.